KAJIAN SOSIOLOGI SASTRA DALAM CERPEN LORONG GELAP KARYA BUDI DARMA (KAJIAN TERHADAP CERPEN KONTEMPORER) - Hesti Endriani (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The Lorong Gelap short story is the work of a well-known Indonesian writer, Budi Darma. This short story can be studied using a sociology of literature approach. The purpose of this study is to describe how people's lives are described by the author in the short story Lorong Gelap. This research was conducted using descriptive analysis method by doing intensive reading on short stories and actively recording with content analysis method. The results of the study indicate that there are five kinds of sociological authors, namely 1) the social status of the author; 2) the author's social ideology; 3) the position of the author in society; 4) the target audience; 5) the author's livelihood and professionalism. In addition, there are also sociological aspects of literary works which include, 1) cultural aspects; 2) socio-political aspects; 3) educational aspects; 4) economic aspects; and 5) religious aspects. As for sociology readers, the book contains social realities in society that can get the attention of readers so that they can appreciate and utilize its values.